En quoi les cartes mentales, appliquées à l’environnement littoral, aident-elles au recueil et à l’analyse des représentations spatiales ? - Servane Gueben-Venière (EchoGéo)
After having been mainly used in urban geography, then cast aside by the geographers, mental maps are now the object of renewed interest, particularly in the field of environmental geography. Applied to the coast, and used as a supplement to the interview, these maps are not only of great assistance in collecting spatial representations, but also helpful in analyzing them. This article uses the example of the integration of mental maps in the scientific poster “Des ingénieurs de plus en plus “verts”. Évolution du regard des ingénieurs en charge de la gestion du littoral néerlandais” ("Engineers are ‘greener and greener’. Evolution of the thinking of engineers in charge of Dutch coastal management"), prize-winner of the competition organized by the Paris Doctoral School of Geography Forum in 2011.